Tính `A = x^10 – 5x^9 + 5x^8 – 5x^7 + …. + 5x^2 – 5x + 1` tại `x = 4`

Tính
`A = x^10 – 5x^9 + 5x^8 – 5x^7 + …. + 5x^2 – 5x + 1` tại `x = 4`

0 thoughts on “Tính `A = x^10 – 5x^9 + 5x^8 – 5x^7 + …. + 5x^2 – 5x + 1` tại `x = 4`”

  1. Đáp án: $A = -3$.

    Giải thích các bước giải:

    Ta có: $x= 4 ⇔ x+1=5$. Thay vào $A$ ta được:

    $A = x^{10} – (x+1).x^9 + (x+1).x^8 – (x+1).x^7 + …. +(x+1).x^2 – (x+1).x + 1$

    $⇔ A = x^{10} – x^{10} – x^9 + x^9 + x^8 – x^8 – x^7 + …. + x^3 + x^2 – x^2 – x + 1$

    $⇔ A = -x + 1$

    $⇔ A = -4 + 1 = -3$.

    Reply
  2. Đáp án:

     

    Giải thích các bước giải:

     `x=4`

    `=>x+1=5`

    `=>A=x^10-x^9(x+1)+x^8(x+1)-x^7(x+1)+…+x^2(x+1)-x(x+1)+1`

    `=x^10-x^10-x^9+x^9+x^8-x^8-x^7+…+x^3+x^2-x^2-x+1`

    `=1-x=1-4=-3`

    Reply

Leave a Comment